Pengaruh Aktivitas Perusahaan Terhadap Profitabilitas - Windawati Windawati; Barlia Annis Syahzuni (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the effect of company activities on profitability, with a focus on industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research population consists of 67 industrial sector companies within the observation period. From this population, the researcher applied purposive sampling criteria, including consistency of listing and the availability of financial statements denominated in rupiah, resulting in the final research sample. With a three-year observation period, the study generated a total of 99 panel data observations. The study employed a quantitative approach, with model selection carried out through the Chow, Hausman, and Lagrange Multiplier (LM) tests. The best model was estimated using the Random Effects model with robust standard errors. The findings indicate that, simultaneously, cash turnover, receivables turnover, and inventory turnover significantly affect profitability. However, when tested partially, receivables turnover show a significant effect on profitability, while cash turnover and inventory turnover does not. In addition, receivables turnover is consistently found to have a significant partial effect on profitability. The managerial implication emphasizes that management should place greater focus on the effectiveness of working capital management, particularly in receivables, cash, and inventory, in an optimal manner. This will enable companies to demonstrate their performance in generating maximum earnings and improving profitability. Furthermore, the information disclosed in financial statements serves as a medium for management to send signals to external stakeholders regarding the company’s future prospects.